Establishmen of maxican beetal (Zygogramma bicolorata) against Parthenium hysterophorus in Marathwada - SARKATE, M B; PAWAR, V M (The Indian Journal of Agricultural Sciences, 2011)
A study was initiated on the biological control of Parthenium hysterophorus L using Mexican beetle, Zygogralnma bieolorata Pallister since 1986-87. Field release and recovery studies indicated spectacular results at Parbhani and Udgir. Beetles defoliated the weed severely thereby indicating the establishment. Mexican beetle has been established in Marathwada region ofmaharashtra.